Impact of Frequency of Financial Reporting on Information Asymmetry and Cost of Equity - Gholam Hossein Assadi (Shahid Bahonar University of Kerman, 2015)
Timeliness of financial reporting is one of the important factors in the quality of firms' financial information, since such are porting can lead to efficient utilization of information for users. Providing more timely information may reduce information asymmetry between acompany and its stockholders. Information asymmetry causes costs of financing from company’s owned sources and from the other sources to be different. This makes financing from the other sources difficult. This study aimed at examining the impacts of financial reporting frequency on information asymmetry and on cost of equity. To measure information asymmetry and cost of equity, the range of bid-ask spread of daily treading, and the ratio of earnings to price were used, respectively. In this study, the data consisted of 71 companies listed in the Tehran Stock Exchange in the period 2006 to 2011, and data analysis and test of hypothesis were carried out by ordinary least squares method. Results showed that there are significant negative relationships between financial reporting frequency, and the variables of information asymmetry and cost of equity. That is, in the years as financial reporting frequency increased, information asymmetry and cost of equity decreased.